1993
DOI: 10.1037/0278-7393.19.4.799
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the total similarity principle: Effects of similarity on frequency judgments.

Abstract: Memory models that embody the total similarity principle (e.g., Gillund & Shiffrin, 1984; Hintzman, 1988; Murdock, 1982; Ratcliff, 1990) assume that frequency judgments reflect the total similarity of a test item to stimuli that have been studied. In 4 experiments, subjects estimated the frequencies of target words that had been presented in the context of varying numbers of semantically similar words. In a fifth experiment, subjects made forced-choice relative frequency judgments. The results of these experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Previous research has demonstrated that the judged frequency or familiarity of a stimulus is a function of both the frequency with which the target stimulus has been presented and the similarity of the stimulus to other, previously encountered stimuli (Jones & Heit, 1993;Nosofsky, 1991). These findings suggest that the familiarity of stimuli encountered in the size reproduction task should depend on the degree to which color was encoded with size information.…”
Section: Methodsmentioning
confidence: 72%
“…Previous research has demonstrated that the judged frequency or familiarity of a stimulus is a function of both the frequency with which the target stimulus has been presented and the similarity of the stimulus to other, previously encountered stimuli (Jones & Heit, 1993;Nosofsky, 1991). These findings suggest that the familiarity of stimuli encountered in the size reproduction task should depend on the degree to which color was encoded with size information.…”
Section: Methodsmentioning
confidence: 72%
“…Most models of induction (e.g., Osherson et al, 1990;Sloman, 1993) have assumed that the generalization of unfamiliar properties is driven by an assessment of the "overall similarity," or amount of feature overlap, between the inductive base and target. This closely parallels the processes that are typically assumed to underlie recognition (Hintzman, 1988;Jones & Heit, 1993;Ratcliff, 1990). Hence, it may not seem all that surprising that Heit and Hayes (2011) found that the overall similarity between old and novel exemplars was important in both tasks.…”
Section: The Relationship Between Recognition and More Complex Forms mentioning
confidence: 70%
“…According to single-process accounts of recognition (e.g., Estes, 1994;Gillund & Shiffrin, 1984;Heit, 1993;Hintzman, 1988;Nosofsky, 1988), judgments are based on a unitary assessment of strength, corresponding to the summed similarity of the test item to all the relevant items in memory. Single-process memory models have been shown to account for a wide variety of data (see Clark & Gronlund, 1996, and Raaijmakers & Shiffrin, 1992, for reviews).A growing body of research, however, suggests that recognition judgments may involve a second, recall-like process (e.g., Atkinson & Juola, 1973Dosher, 1984;Gronlund & Ratcliff, 1989;Hintzman & Curran, 1994;Humphreys, 1978;Jacoby & Dallas, 1981;Jones & Heit, 1993;Mandler, 1980;Ratcliff & McKoon, 1982, 1989Yonelinas, 1994; see Mandler, 1991, for a brief review). For example, one dual-process account assumes rhar recognition decisions are based on the familiarity of the target item if that familiarity is either sufficiently strong or suf-…”
mentioning
confidence: 99%
“…A growing body of research, however, suggests that recognition judgments may involve a second, recall-like process (e.g., Atkinson & Juola, 1973Dosher, 1984;Gronlund & Ratcliff, 1989;Hintzman & Curran, 1994;Humphreys, 1978;Jacoby & Dallas, 1981;Jones & Heit, 1993;Mandler, 1980;Ratcliff & McKoon, 1982, 1989Yonelinas, 1994; see Mandler, 1991, for a brief review). For example, one dual-process account assumes rhar recognition decisions are based on the familiarity of the target item if that familiarity is either sufficiently strong or suf-…”
mentioning
confidence: 99%